Strawberry (Fragaria × ananassa cv. Romina) methanolic extract promotes browning in 3T3-L1 cells. Issue 1 (9th January 2020) - Forbes-Hernández, Tamara Y.; Cianciosi, Danila; Ansary, Johura; Mezzetti, Bruno; Bompadre, Stefano; Quiles, Josè L.; Giampieri, Francesca; Battino, Maurizio
Abstract : The conversion of white adipocytes to brown-like adipocytes by pharmacological and dietary compounds has gained attention as an effective strategy to fight obesity. Abstract : In recent years, the conversion of white adipocytes to brown-like adipocytes by pharmacological and dietary compounds has gained attention as an effective strategy to fight obesity. Strawberry bioactive compounds present several biological activities including antioxidant, anti-inflammatory, anti-cancer, anti-atherosclerotic and antiadipogenic properties. However, to the best of our knowledge, the possible role of strawberry bioactive compounds in white adipose tissue (WAT) browning has never been explored. Our results demonstrated that a strawberry methanolic extract (SE) significantly reduced 3T3-L1 pre-adipocytes differentiation, and down-regulated the mRNA expression of the adipogenic transcription factors CCAAT/enhancer-binding protein (C/REB- α) and peroxisome proliferation-activated receptor (PPAR-γ). It also down-regulated the mRNA expression of resistin and angiotensinogen, two genes considered as markers of white adipocytes, while increased the mRNA expression of pyruvate dehydrogenase lipoamide kinase isozyme 4 (PDK4) and uncoupling protein 1 (UCP1) which, conversely, are brown adipocyte-specific markers. Likewise, SE stimulated AMP-activated protein kinase (AMPKα), sirtuin 1 (Sirt1) and the peroxisome proliferator activated receptor gamma coactivator 1-alpha (PGC-1α), suggesting a possible increase in mitochondrial biogenesis. It also stimulated oxygen consumption rate and uncoupled respiration. Taken together, all these results suggest that SE induces brown fat-like phenotype in 3T3-L1 cells and may have potential therapeutic implications for treatment and/or prevention of obesity.